2021
DOI: 10.1101/2021.03.15.21253597
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Hospitalisation rates differed by city district and ethnicity during the first wave of COVID-19 in Amsterdam, the Netherlands

Abstract: Background It is important to gain insight into the burden of COVID-19 at city district level to develop targeted prevention strategies. We examined COVID-19 related hospitalisations by city district and migration background in the municipality of Amsterdam, the Netherlands. Methods We used surveillance data on all PCR-confirmed SARS-CoV-2 hospitalisations in Amsterdam until 31 May 2020, matched to municipal registration data on migration background. We calculated directly standardised (age, sex) rates (DSR) … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
2

Relationship

3
2

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 17 publications
0
10
0
Order By: Relevance
“…Survival bias among the retrospectively-enrolled hospitalised participants may have caused an underestimation of time to complete recovery in those with severe/critical disease, although results were comparable when restricting our analyses to prospectively identified participants. Questionnaires in languages other than Dutch and English were not offered, therefore individuals with a migration background, who have been disproportionally affected by COVID-19, also in Amsterdam[25, 26], were underrepresented in this cohort. Furthermore, misclassification bias may have resulted from using ICU admission as a proxy for critical disease; suitability for ICU admission is also judged by the patient’s chance of survival; indeed, those with critical disease tended to be younger and have a lower BMI than those in the severe group.…”
Section: Discussionmentioning
confidence: 99%
“…Survival bias among the retrospectively-enrolled hospitalised participants may have caused an underestimation of time to complete recovery in those with severe/critical disease, although results were comparable when restricting our analyses to prospectively identified participants. Questionnaires in languages other than Dutch and English were not offered, therefore individuals with a migration background, who have been disproportionally affected by COVID-19, also in Amsterdam[25, 26], were underrepresented in this cohort. Furthermore, misclassification bias may have resulted from using ICU admission as a proxy for critical disease; suitability for ICU admission is also judged by the patient’s chance of survival; indeed, those with critical disease tended to be younger and have a lower BMI than those in the severe group.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, data from ongoing studies of the general population spread of the virus [ 4 ] suggest that a higher risk of exposure is associated with socio-economic vulnerabilities, such as limited educational and employment opportunities and/or belonging to an ethnic minority, and that people in poorer general health are more likely to develop severe and fatal illness [ 5 – 8 ]. It has also been observed that immigrants are at greater risk of exposure and infection than native populations, probably because they often work in high-risk occupations, live in overcrowded accommodation, and face barriers to healthcare and prevention initiatives [ 9 , 10 ]. Some studies have found that immigrants with COVID-19 are also at increased risk of hospitalisation [ 9 , 10 ], but it is unclear whether this means that they are also at increased risk of COVID-19-related death [ 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…It has also been observed that immigrants are at greater risk of exposure and infection than native populations, probably because they often work in high-risk occupations, live in overcrowded accommodation, and face barriers to healthcare and prevention initiatives [ 9 , 10 ]. Some studies have found that immigrants with COVID-19 are also at increased risk of hospitalisation [ 9 , 10 ], but it is unclear whether this means that they are also at increased risk of COVID-19-related death [ 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…The increased preventive measures during church services could have offered reduced SARS-CoV-2 transmission. Given the higher rates per population observed in SARS-CoV-2 incidence, as well as hospitalization and mortality in ethnic minority groups, 1,2,22 which were also apparent in Amsterdam, 4 sustained and targeted actions to reduce these disparities are warranted. With the wide availability of safe and effective vaccines against SARS-CoV-2, it is imperative to achieve high vaccination uptake, particularly in populations at high risk of SARS-CoV-2 infection and unfavorable outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Higher rates of SARS-CoV-2 diagnoses were observed in ethnic minority groups, in particular people of African and Asian descent, during the first wave of the SARS-CoV-2 epidemic in the United Kingdom, United States, and much of Europe. [1][2][3][4] SARS-CoV-2 seroprevalence estimates in England and the United States continued to increase in individuals of African and Asian descent during late 2020 and early 2021. 5,6 These disparities have been related to ethnic differences in household composition, occupations requiring use of public transportation, and increased exposure to crowded conditions.…”
Section: Introductionmentioning
confidence: 99%